A 15ps resolution time-to-digital converter with on-chip PLL counting for LiDAR multi-object sensors. (October 2019) - Duan, Jiangkun; Liu, Maliang; Zhu, Zhangming; Yang, Yintang
Abstract: Light detection and ranging (LiDAR), as a kind of depth image processing technology, has a wide range of applications in precise range and range rate equipment (PRARE) and two-dimensional/three-dimensional imaging systems. This paper presents a high resolution time-to-digital converter (TDC) for LiDAR sensors. The count clock provided by the on-chip phase-locked loop (PLL) guarantees high resolution and reliable PVT (process, voltage and temperature) tolerance of the TDC. In particular, a novel structure of a pulse-injection ring oscillator shared by TDC and PLL is proposed to avoid frequency offsets and clock jitter caused by the use of multiple ring oscillators while saving power consumption. To satisfy the LiDAR for adjacent multi-object sensing, a fast digital shift register array is introduced. Other key circuits considered to reduce the non-linearity and bit error of TDC are described in detail. The prototype chip is fabricated in a standard 65 nm CMOS process with an area of 0.056 mm 2 . Using a 1.2 V supply, the TDC achieves an average power consumption of 3.36 mW. The performance of the TDC has been measured. The maximum differential nonlinearity (DNL) is 13.4ps and the maximum integral non-linearity (INL) is 32.1ps with the help of INL LUT calibration, respectively.